Examining the Role of Social Trust in the Angel Investors’ Decision-Making Process: The Case of Egypt - Elhady, Salma (AUC Knowledge Fountain, 2016)
This study focuses on examining the role of trust in the angel investors’ decision-making process. It was developed with the aim to advance understanding of the relationship between social trust and angel investments in a developing country such as Egypt and to examine the implications on transaction cost. Studying angel investment in the Egyptian context is important due to the existing boom in entrepreneurship in the country, lack of access to finance, and the nature of the economic ecosystem in Egypt shaped by cultural and social ties. The importance of these types of investors to the economic growth and sustainability of the entrepreneurial ecosystem is the main motive to examine angel investors’ decision-making processes. This study was conducted using in depth semi-structured interviews with ten angel investors located in Egypt. The findings of this study disassociated trust from social capital, which contradicts views of extant work and was more aligned with the notion that trust is a collective asset built from working on social capital. Further, the findings of this study highlighted the role of feelings and emotions as a key decision-making factor contributing to the evolution of the angel – entrepreneur relationship during the decision-making process. In this study, participants used ‘marriage’ and ‘friendship’ as a metaphor to their relationship with the entrepreneur, reflecting the emotional dimension they confer to their interactions with the entrepreneurs. These findings resonate with existing literature, though sparse, illustrating that the investor’s internal emotional or mood state, while taking an investment decision, could affect their judgment as well as their behavior to allocate equity towards a company. This work extends existing research by furthering understandings that angel investors associate emotions with their decisions, not only at the equity allocation phase and while making the final decision but also throughout the different pre-investment activities. Moreover, their perception of trust and how it relates to moving from one stage to another or even surpassing certain stages had an emotional dimension triggering the decision. Interestingly and of theoretical importance, angels in this study conceptualized trust as feelings and emotions; referring to trusting an entrepreneur or deciding to invest in certain venture, as a ‘gut’ feeling. Taking into consideration the aforementioned findings, this study suggests integrating non-economic factors such as trust and emotions into the angel investment process, specifically in the decision-making process to accommodate the impact of emotions and gut feelings.